Occurrence of deoxynivalenol in maize germs from North China Plain and the distribution of deoxynivalenol in the processed products of maize germs. (15th November 2018) - Xu, Li-Li; Wen, Yun-Qi; Liu, Yu-Lan; Ma, Yu-Xiang
Highlights: The contamination rate of DON in maize germ is as high as 95.7%. Pressing has a less DON transfer into corn oil compared with solvent extraction. The consumption of corn oil from China has lower-risk of DON for consumers. Abstract: 69 maize germ samples from North China Plain, 40 processed products of maize germs obtained in lab, 30 crude corn oils from factories and 40 refined corn oils from supermarkets in China were analyzed of deoxynivalenol (DON) by HPLC combined with ultraviolet detection and immunoaffinity column. 95.7% of maize germs were contaminated by DON. The average content was 449.0 μg/kg. The average of DON in processed products of maize germs including solvent extracted oil, cold-press oil, meal and cake was 163.7, 113.1, 1111.5 and 1175.2 μg/kg, respectively. Only 20% of crude corn oil and 12.5% of refined corn oil were contaminated by DON with the range of 67.5–340.5 μg/kg and 57.1–207.5 μg/kg, respectively. During the production of corn oil, solvent extraction oil had a larger amount of DON than pressing oil. The contamination of DON in corn oil was not serious or widespread, which indicated a low risk of health.